ESRα Promoter Methylation May Modify the Association Between Lipid Metabolism and Type 2 Diabetes in Chinese Farmers - Zhou, Guoyu; Liu, Lihua; Li, Xing; Hou, Xiangbo; Wang, Ling; Sun, Renjie; Huang, Hui; Li, Zhiyuan; Li, Wenjie; Wang, Chongjian; Ba, Yue (Frontiers in Public Health, 2021)
Objective: To explore the potential association among the estrogen receptor alpha (ESRα) promoter methylation, lipid metabolism and the risk of type 2 diabetes mellitus (T2DM). Methods: A total of 1143 resident adults (aged 35-74 years) were recruited randomly from rural areas in Henan Province, China. The levels of ESRα promoter methylation were determined by quantitative methylation-specific polymerase chain reaction. Serum high density lipoprotein (HDL-C), low density lipoprotein (LDL-C), triglyceride (TG), total cholesterol (TC) and fasting plasma-glucose (FPG) were measured using automatic biochemical analyzer. Results: The ESRα promoter methylation levels were negatively associated with HDL-C levels whether gender stratification was performed (P < 0.05) and positively correlated with LDL-C in men (P < 0.05). Each SD increment in TG was associated with a 43% increase (95% CI: 1.25, 1.64) in the risks of T2DM in all participants, a 36% increase (95% CI: 1.13, 1.64) in the risks of T2DM in men and a 49% increase (95% CI: 1.21, 1.83) in the risks of T2DM in women. Furthermore, each SD increment in HDL-C was associated with a reduction of 25% (OR = 0.75, 95% CI: 0.58, 0.97) in the risks of T2DM in men, and the risk of T2DM in men may be more susceptible to HDL-C than that in women (P for interaction < 0.05). Additionally, we found that the risk of T2DM in participants with lower methylation (≤ 4.07%) were more susceptible to HDL-C (P for interaction < 0.05). Conclusions: Our findings suggested that lipid metabolism was associated with ESRα promoter methylation levels and the risk of T2DM. Besides, the levels of ESRα promoter methylation and gender can modify the association of HDL-C and T2DM.